The Contribution of Employability Skills to Career Adaptability in Final-Year Students - Tandiayuk, Suryadi; Fabiola Susanto, Angie; Bellani, Elvita (Manunggal Halim Jaya, 2022)
This study aims to determine the contribution of employability skills to the career adaptability of final-year students at Universitas Hasanuddin. The subjects in this study were 336 people aged 20–24 years and were taken based on accidental sampling techniques. Data was collected by deploying Graduate Skills and Attribute Scales (GSAS) and Career Adaptability Scales (CAAS). The data were analyzed by simple linear regression. The simple linear regression test results showed a significant value of 0.000 (p > 0.05), which showed that employability skills contributed significantly to career adaptability in final year students of Universitas Hasanuddin. The coefficient of determination value is 0.412, meaning that employability skills contribute 41.2% to the career adaptability of final-year students at Universitas Hasanuddin. This means that final-year students must develop their skills to adapt to their career choices.